Vascular function and stiffness: population epidemiology and concordance in Australian children aged 11–12 years and their parents. (4th July 2019) - Kahn, Freya K; Wake, Melissa; Lycett, Kate; Clifford, Susan; Burgner, David P; Goldsmith, Greta; Grobler, Anneke C; Lange, Katherine; Cheung, Michael
Abstract : Objectives: To describe the epidemiology and parent–child concordance of vascular function in a population-based sample of Australian parent–child dyads at child age 11–12 years. Design: Cross-sectional study (Child Health CheckPoint), nested within a prospective cohort study, the Longitudinal Study of Australian Children (LSAC). Setting: Assessment centres in seven major Australian cities and eight regional towns or home visits, February 2015–March 2016. Participants: Of all participating CheckPoint families (n=1874), 1840 children (49% girls) and 1802 parents (88% mothers) provided vascular function data. Survey weights and methods were applied to account for LSAC's complex sample design and clustering within postcodes and strata. Outcome measures: The SphygmoCor XCEL assessed vascular function, generating estimates of brachial and central systolic blood pressure and diastolic blood pressure, central pulse pressure, augmentation index and carotid–femoral pulse wave velocity. Pearson's correlation coefficients and multivariable linear regression models estimated parent–child concordance. Results: Hypertension was present in 3.9% of children and 9.0% of parents. Mean child and parent values for augmentation index were 4.5% (SD 11.6) and 21.3% (SD 12.3), respectively, and those for carotid–femoral pulse wave velocity were 4.48 m/s (SD 0.59) and 6.85 m/s (SD 1.14), respectively. Parent–child correlation for brachial systolic blood pressure was 0.20 (95% CI 0.15 to 0.24), brachial diastolic blood pressure 0.21 (95% CI 0.16 to 0.26), central systolic blood pressure 0.21 (95% CI 0.16 to 0.25), central diastolic blood pressure 0.21 (95% CI0.17 to 0.26), central pulse pressure 0.19 (95% CI 0.14 to 0.24), augmentation index 0.28 (95% CI 0.23 to 0.32) and pulse wave velocity 0.22 (95% CI 0.18 to 0.27). Conclusions: We report Australian values for traditional and more novel vascular function markers, providing a reference for future population studies. Cross-generational concordance in multiple vascular function markers is already established by age 11–12 years, with mechanisms of heritability remaining to be explored.